Binge drinking and alcohol related hospital stays: Does a legal drinking age matter for minors? - Fabian Dehos; Anne Mensen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
This paper evaluates the effectiveness of the German Minimum Legal Drinking Age in reducing excessive drinking and alcohol-related hospital stays. We add to previous studies by looking at a considerably earlier cutoff at age 16, when teenagers in Germany gain legal access to beer, wine, and sparkling wine. Using detailed survey data, we find considerable increases in moderate alcohol consumption and self-perceived drunkenness at age 16, but rather negligible effects for excessive drinking patterns which may lead to coma or deaths. Likewise, our analysis of daily-hospital-admission data reveals no discontinuities in hospital stays due to acute alcohol intoxication. Admissions due to physical injuries, in contrast, increase by about 11% at age 16 which coincides with teenage drinking patterns and incidents when drunken teenagers fall or get into a fight. – – Die vorliegende Studie analysiert die Wirksamkeit der deutschen Alterszugangsbeschränkungen zu Alkohol auf exzessives Trinkverhalten und alkoholbedingte Krankenhauseinlieferungen. Wir ergänzen bestehend Studien insofern, als wir eine besonders niedrige Altersgrenze von 16 Jahren untersuchen, ab der Jugendliche in Deutschland legal Zugang zu Bier, Wein und Sekt erhalten. Detaillierte Umfragedaten zeigen eine erhebliche Zunahme des moderaten Konsums und der selbst wahrgenommenen Trunkenheit im Alter von 16 Jahren, jedoch eher vernachlässigbare Auswirkungen auf exzessives Trinkverhalten, das zu Koma oder Todesfällen führen kann. Unsere Analyse tagesgenauer Krankenhausdaten zeigt ebenfalls keine Veränderung bei Einlieferungen aufgrund akuter Alkoholvergiftung. Krankenhauseinlieferungen aufgrund physischer Verletzungen hingegen steigen mit 16 Jahren um etwa 11% an; dies stimmt mit jugendlichen Trinkgewohnheiten überein und geht mit Vorfällen einher, bei denen betrunkene Teenager stürzen oder in eine Schlägerei geraten.
Keywords: I12; I18; J13; K32; 330; Alcohol; minimum legal drinking age; binge drinking; hospital admissions